Hydromechanical stimulator for chondrocyte-seeded constructs in articular cartilage tissue engineering applications. (March 2013) - Pourmohammadali, Homeyra; Chandrashekar, Naveen; Medley, John B
Mechanical stimulation is a key technique used for controlling the mechanical properties of tissue engineered articular cartilage constructs proposed for defect repair. The present study introduces a new technical method and device for 'hydromechanical' stimulation of tissue engineered articular cartilage constructs. The stimulation consists of simultaneous cyclic compression, frictional shear from a sliding indenter contact and direct pressurized fluid perfusion. Each of these modes of mechanical loading has been shown by other research groups to effectively stimulate tissue engineered constructs. A device for applying these conditions was designed, developed and tested. Two sets (high and low perfusion flow rates) of three experiments were performed, each with two samples subjected to hydromechanical stimulation conditions (compression and friction forces along with perfusion). Two other samples from each set were subjected to just compression and dynamic frictional shear forces, and two more were used as controls (not stimulated). The average amount of glycosaminoglycan retained in the constructs after 3 weeks ranked from low to high as follows: controls, hydromechanical conditions with the low-flow rate, hydromechanical conditions with the high-flow rate and just compression plus dynamic frictional shear. Statistically significant differences were not detected. However, future studies would focus on glycosaminoglycan production in the superficial zone, measuring the glycosaminoglycan released to the nutrient media, and address altering the hydromechanical stimulation parameters using the results of the present study as guidance, in attempts to achieve statistically significant increases in glycosaminoglycan production compared with the controls.